Customizable Lipid Nanoparticle Materials for the Delivery of siRNAs and mRNAs. Issue 41 (14th September 2018) - Fenton, Owen S.; Kauffman, Kevin J.; McClellan, Rebecca L.; Kaczmarek, James C.; Zeng, Manhao D.; Andresen, Jason L.; Rhym, Luke H.; Heartlein, Michael W.; DeRosa, Frank; Anderson, Daniel G.
Abstract: RNAs are a promising class of therapeutics given their ability to regulate protein concentrations at the cellular level. Developing safe and effective strategies to deliver RNAs remains important for realizing their full clinical potential. Here, we develop lipid nanoparticle formulations that can deliver short interfering RNAs (for gene silencing) or messenger RNAs (for gene upregulation). Specifically, we study how the tail length, tail geometry, and linker spacing in diketopiperazine lipid materials influences LNP potency with siRNAs and mRNAs. Eight lipid materials are synthesized, and 16 total formulations are screened for activity in vitro; the lead material is evaluated with mRNA for in vivo use and demonstrates luciferase protein expression in the spleen. In undertaking this approach, not only do we develop synthetic routes to delivery materials, but we also reveal structural criteria that could be useful for developing next‐generation delivery materials for RNA therapeutics. Abstract : Deliver as required : Lipid nanoparticle formulations were developed that can deliver short interfering RNAs (for gene silencing) or messenger RNAs (for gene upregulation). Eight lipid materials are synthesized, and 16 total formulations are screened for activity in vitro; the lead material is evaluated with mRNA for in vivo use and demonstrates luciferase protein expression in the spleen.